Synthesis and XRD of neutral NiL complex using unsymmetrical ONNO tetradentate schiff base: Hirschfeld, spectral, DFT and thermal analysis. Issue 8 (17th April 2020) - Said, Musa A.; Qasem, Hamza A.; Alzahrani, Seraj O.; Zarrouk, Abdelkader; Warad, Ismail
Abstract: The unsymmetrical tetradentate ONNO Schiff base 6, 6'-((1E, 1'E)-((2-methylpropane-1, 2-diyl)bis(azanylylidene))bis(methanylylidene))bis(2, 4-di-tert-butylphenol) (H2 L ) was prepared following a slightly modified known condensation reaction. The neutral NiL complex has been synthesized in high yield via [1H2 L:1Ni(II)] direct addition. The XRD-measurement reflects a Ni II center with slightly distorted square planar geometry. Moreover, the lattice is stabilized by a number of H-bond and H… π stacking interactions. The structure connections have been illustrated by electrostatic potential surface (Molecular Electrostatic Potential, MEP) and Hirschfeld surface (HSA) and Fingerprint (FP) analysis to support such interactions. IR and UV-visible spectra were measured to compare free H2 L with NiL behaviors. The DFT-optimized structure was compared to the XRD-structure parameters. NiL reflects high thermal stability and decomposed mainly via one-step to form NiO as the final product. Graphical Abstract: